2019
DOI: 10.1002/jcp.28345
|View full text |Cite
|
Sign up to set email alerts
|

Targeting autophagy in cardiac ischemia/reperfusion injury: A novel therapeutic strategy

Abstract: Acute myocardial infarction (AMI) is one of the leading causes of morbidity worldwide. Myocardial reperfusion is known as an effective therapeutic choice against AMI. However, reperfusion of blood flow induces ischemia/reperfusion (I/R) injury through different complex processes including ion accumulation, disruption of mitochondrial membrane potential, the formation of reactive oxygen species, and so forth. One of the processes that gets activated in response to I/R injury is autophagy. Indeed, autophagy acts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 121 publications
(201 reference statements)
2
51
0
Order By: Relevance
“…Under short-term hypoxia and starvation conditions, autophagy is activated and plays a dual regulatory role. 48 Epicatechin gallate can protect HBMVECs from IR injury by ameliorating apoptosis and autophagy, but Alliin alleviates myocardial IR injury by promoting autophagy. 49,50 Initial autophagy is an important defence mechanism to remove damaged cell structures and aging organelles from degraded cells.…”
Section: Discussionmentioning
confidence: 99%
“…Under short-term hypoxia and starvation conditions, autophagy is activated and plays a dual regulatory role. 48 Epicatechin gallate can protect HBMVECs from IR injury by ameliorating apoptosis and autophagy, but Alliin alleviates myocardial IR injury by promoting autophagy. 49,50 Initial autophagy is an important defence mechanism to remove damaged cell structures and aging organelles from degraded cells.…”
Section: Discussionmentioning
confidence: 99%
“…21 In view of this, there has been a growing interest in developing novel protective stimuli applied at the onset of IR to limit subsequent injury. 22 Among these treatments, melatonin-a pleiotropic hormone produced mainly by the pineal gland-has gained much attention. 23 In a clinical trial, Fatemeh and colleagues showed that oral melatonin in renal transplant patients leaded to a significant reduction in complications related to IR injury and renal function markers such as BUN/ creatinine ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial ischemia/reperfusion (I/R) injury is a major contributing factor of morbidity and mortality in patients with ischemic heart disease or after cardiac surgery. 1,2 Studies identified various molecular and cellular mechanisms involved in the process of myocardial I/R. [3][4][5][6][7] Of these, intracellular calcium [Ca 2+ ]i overload is a critical one that leads to cardiomyocyte apoptosis and cell death.…”
Section: Introductionmentioning
confidence: 99%